2018
DOI: 10.1007/s11240-018-1507-5
|View full text |Cite
|
Sign up to set email alerts
|

Explant type and stress treatment determine the uni- and multicellular origin of somatic embryos in the tree fern Cyathea delgadii Sternb.

Abstract: Cyathea delgadii is the first fern species for which somatic embryogenesis (SE) has recently been described. With this discovery, a new experimental model for exploration of SE was found. In this study, the effect of explant type (stipe and internode), length and diameter of the explant-donor frond, and stress treatment (by sucrose and air desiccation) on somatic embryo origin and SE efficiency was studied. In control culture, somatic embryos originated from single cells of stipe explants, whereas those induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…Different studies support the theory that the first stages of SE are characterized by the induction of numerous genes related to stress such as those discussed later on this review (Nic-Can et al, 2016; Nowak and Gaj, 2016). Recent evidence in potato (Kaur et al, 2018), Pinus sylvestris (Salo et al, 2016), Picea asperata (Jing et al, 2017), Oldenlandia umbellata (Krishnan and Siril, 2017), and Cyathea delgadii (Grzyb and Mikula, 2019) has revealed that the presence of different types of stress plays an essential role in the induction of SE. The main stress for cells during the induction of SE is the presence of high auxin concentration in the culture medium.…”
Section: Stress and Somatic Embryogenesismentioning
confidence: 99%
“…Different studies support the theory that the first stages of SE are characterized by the induction of numerous genes related to stress such as those discussed later on this review (Nic-Can et al, 2016; Nowak and Gaj, 2016). Recent evidence in potato (Kaur et al, 2018), Pinus sylvestris (Salo et al, 2016), Picea asperata (Jing et al, 2017), Oldenlandia umbellata (Krishnan and Siril, 2017), and Cyathea delgadii (Grzyb and Mikula, 2019) has revealed that the presence of different types of stress plays an essential role in the induction of SE. The main stress for cells during the induction of SE is the presence of high auxin concentration in the culture medium.…”
Section: Stress and Somatic Embryogenesismentioning
confidence: 99%
“…Plant somatic embryogenesis (SE) is a unique developmental process that ultimately leads to the regeneration of a whole plant from single or multiple somatic cells [ 1 ]. This process involves sophisticated cellular reprogramming events that are controlled by gene expression programs and signaling pathways that direct callus cells to dedifferentiate, reprogram, and begin differentiation into polarized structures that eventually become a viable embryo [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathway of somatic embryo initiation and development in C. delgadii explants depends on such artless factors as length and diameter of the explant-donor frond, type of explant, as well as physical and chemical factors of media and culture conditions ( Mikuła et al. 2015a , Grzyb and Mikuła, 2019 ). One of the basic triggers inducing SE is the light conditions for donor plantlet growth ( Mikuła et al.…”
Section: Introductionmentioning
confidence: 99%